2004
DOI: 10.3151/jact.2.419
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Peeling Failure in Plated Beams

Abstract: Peeling failure is one of the main drawbacks of reinforced concrete (RC) members strengthened by externally bonded plates. Two different techniques are suggested to prevent peeling failure at the ends of steel plates glued to the soffits of RC beams. In the first technique, concrete cover is replaced by grout to enhance the resistance of substrate to crack initiation and propagation. In the second technique, permanent compressive forces at the ends of bonded plate are applied using different plate end anchorag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…By increasing the applied load, the coalesced crack will propagate till failure point, as shown in Fig.6. A similar behavior was observed by (Sallam et al 2004;Yehia and Wahab 2007) for pre-cracked Reinforced concrete beams under mode I, at which, the pre-crack propagated at a load equal to that of smooth specimens at the same crack length.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…By increasing the applied load, the coalesced crack will propagate till failure point, as shown in Fig.6. A similar behavior was observed by (Sallam et al 2004;Yehia and Wahab 2007) for pre-cracked Reinforced concrete beams under mode I, at which, the pre-crack propagated at a load equal to that of smooth specimens at the same crack length.…”
Section: Resultssupporting
confidence: 78%
“…Fracture mechanics concepts were successfully applied on propagating cracks under mode I (opening mode). Sallam et al (2004) proved that, the behavior of pre-cracked specimen is identical to that of smooth specimen when the generated crack in the smooth specimen reaches an equal length as that of the pre-cracked one. The behavior of both specimens is different at the stage before generating the first crack till it reaches the pre crack length.…”
Section: Introductionmentioning
confidence: 90%
“…Hybrid bonded FRP technique [26] and U-anchor system [27] are suggested to prevent such type of failure. Sallam et al [2] found that cover separation or debonding failure in EB system can be prevented by concrete cover replacement technique.…”
Section: Introductionmentioning
confidence: 98%
“…Although the use of EB technique increases the load carrying capacity of the RC strengthened members, the NSM FRP strengthening technique offers many advantages over EB. These advantages include increasing bond capacity due to larger bonded surface area and make a protection against external damage results from external impacts, since the bar is embedded in the concrete cover [1,2]. Although the researches indicated that the EB and NSM techniques are effective techniques for increasing both flexural and shear capacity of structural members [3][4][5][6], the failure due to debonding of FRP reinforcement is still the most common failure mode [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Raoof et al (2000) were able to establish that the premature plate peeling failure can be prevented by increasing the concrete strength, the ratio of the beam width to the plate width, the diameters of the internal tension rebars, and the number of layers of tension reinforcement. The experiments conducted by Sallam et al (2004) indicated that the ductility of a plated RC beam can be improved by replacing the cover concrete in the plate curtailment regions with a grout of higher strength or applying initial compressive stresses to the plate by pressing it against the beam with the help of clamps or bolts. Arslan et al (2008) experimentally showed that the contribution of collar anchorage of the plate ends to ductility stems from the resistance provided by the collars to crack propagation at the plate curtailment locations.…”
Section: Introductionmentioning
confidence: 99%